The UN Security Council and prevention of displacement - Sanjula Weerasinghe; Elizabeth Ferris (Forced Migration Review, 2012)
Respecting the prohibitions against forced and arbitrary displacementcould significantly reduce the risk of, or prevent, displacement insituations of armed conflict, as could insisting on accountabilityfor violations of these prohibitions that amount to war crimes orcrimes against humanity. The UN Security Council has only partiallyaddressed these issues.